Iron(III) and nickel(II) complexes of O,N,N,O-chelating benzophenone thiosemicarbazone: Electrochemistry and in situ spectroelectrochemistry - KOCA, ATIF (ELSEVIER SCIENCE SA, 2012)
New complexes, [Fe(L)Cl] (1 and 2) and [Ni(L)]center dot C2H5OH (3 and 4), were synthesized by template condensation of 2,4-dihydroxy-benzophenone-S-methyl-thiosemicarbazone with 5-bromo- and 5-chloro-2-hydroxy-benzaldehyde and characterized by elemental analysis, conductivity measurements, IR, NMR and mass spectra. Complex 4 crystallizes in monoclinic space group P2(1)/c with unit cell dimensions, a = 13.1091 (3) angstrom, b = 24.2308 (3) angstrom, c = 15.5808 (4) angstrom, beta = 102.2632 (11)degrees, V = 4836.22 (18) angstrom(3), Z = 8. The asymmetric unit of 4 contains two main molecules and two ethanol molecules. Electrochemical behaviors of 1-4 were studied using cyclic voltammetry and square wave voltammetry. Voltammetric analysis of the complexes shows a quasi-reversible metal-based reduction processes between -0.55 and -0.78 V followed by an irreversible reduction process within -0.91 and -1.27 V versus SCE. An irreversible oxidation is also observed within -1.10 to -1.23 V versus SCE during anodic potential scans. While the thiosemicarbazone moiety stabilizes +3 and +2 oxidation states for the iron complexes, only Ni-II is stable in solution with the same ligand in dichloromethane and dimethylsulfoxide. In-situ spectroelectrochemical studies were employed to determine the colors and spectra of electrogenerated species of the complexes. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Thiosemicarbazone; ONNO complexes; Electrochemistry; Spectroelectrochemical analysis; X-ray analysis; CRYSTAL-STRUCTURE; METAL-COMPLEXES; DIOXOMOLYBDENUM(VI) COMPLEXES; PLATINUM(II) COMPLEXES; 2-ACETYL PYRIDINE; REDOX PROPERTIES; SPECTROSCOPY; DINUCLEAR; MONONUCLEAR; COPPER(II)